An African assertion? - Doxtader, Erik (Javnost (Ljubljana), 2005)
In the last decade, the idea and practice of reconciliation has come to play an important, if not central, rhetorical role in the international discourse of nation building and democratisation. This development marks an African assertion in terms of international relations. Focused primarily on the South African transition from apartheid to non-racial democracy, this essay reflectson reconciliation's current global currency, the ways in which it has complicated standing norms of political subjectivity and international law, and how the rhetorical operativity of reconciliation may stand in significant opposition to the logic of emergency that increasingly defines the west's approach to international "relations."
Keywords: Južna Afrika; South Africa; Južnoafriška republika; tranzicija; demokratizacija; democracy; demokracija; mednarodni odnosi; komuniciranje; communication; politične komunikacije